Frit-based controller tuning of a dc-dc boost converter - Amirudin, Zulkepli (2022)
This report presents a Fictitious Reference Iterative Tuning design for a DC-DC boost converter based on a Model-Free approach. A Fictitious Reference Iterative Tuning is a data-driven controller tuning technique that uses one-shot experimental data to construct the input controller of an undefined plant model. Fictitious Reference Iterative Tuning ensures that the plant output fits the reference model output by optimizing the performance index, which comprises a fictional reference output calculated from oneshot experimental input-output results. A DC-DC boost converter is a step-up converter with an output voltage higher than the input voltage. This converter system has a nonlinear dynamic behaviour, as it works in switch mode. The modelling of a Boost converted system is first provided to form data collection and fictitious reference signal derivation. The configuration of a nonlinear system discussed here is assumed to be known, but the parameters remain unknown. Design and simulation analyses using MATLAB software have been conducted for results validation and verification. Furthermore, we formulate the algorithm for determining the optimal controller parameters based on the Model-Free approach. Lastly, we verify and compare the proposed tuning technique’s output with any controller design techniques.